2014
DOI: 10.1007/s10681-014-1266-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait locus mapping for seed dormancy in different post-ripening stages in a Tibetan semi-wild wheat (Triticum aestivum ssp. tibetanum Shao)

Abstract: Tibetan semi-wild wheat (Triticum aestivum ssp. tibetanum Shao) is a hexaploid wheat resource distributed only in Tibet that has an interesting type of seed dormancy in addition to hulled glumes and brittle spikelets. A whole-genome linkage map of T. aestivum ssp. tibetanum was constructed for a population of 186 recombinant inbred lines using 645 diversity array technology (DArT) markers, 127 simple sequence repeat markers and three R-1 genotyping markers. Seed dormancy was evaluated at five postripening stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Our study has provided a new example from a polyploid species, hexaploid wheat, enabling a comparison of the de‐domestications of rice and wheat. Brittle rachises (equivalent to seed shattering in rice) (Cao et al ., ; Chen et al ., ; Jiang et al ., ) and seed dormancy (Lan et al ., ; Jiang et al ., ) are typical features of both Tibetan semi‐wild wheat and weedy rice. In weedy rice, the re‐acquisition of seed shattering was driven by novel genes resulting from mutations (Thurber et al ., ; Subudhi et al ., ; Qi et al ., ; Yao et al ., ), and the development of seed dormancy was due to both pre‐existing variations and new mutations (Gross et al ., ; Xia et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study has provided a new example from a polyploid species, hexaploid wheat, enabling a comparison of the de‐domestications of rice and wheat. Brittle rachises (equivalent to seed shattering in rice) (Cao et al ., ; Chen et al ., ; Jiang et al ., ) and seed dormancy (Lan et al ., ; Jiang et al ., ) are typical features of both Tibetan semi‐wild wheat and weedy rice. In weedy rice, the re‐acquisition of seed shattering was driven by novel genes resulting from mutations (Thurber et al ., ; Subudhi et al ., ; Qi et al ., ; Yao et al ., ), and the development of seed dormancy was due to both pre‐existing variations and new mutations (Gross et al ., ; Xia et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Qbr.sau-5A, Br1 3D and Qbr.sau-2D2) for the brittle rachis trait, suggesting that Tibetan semi-wild wheat regained seed dispersal mechanisms through new mutations during de-domestication. In the same mapping population, Jiang et al (2015) identified seven QTL associated with seed dormancy, two of which are unique to Tibetan semi-wild wheat, indicating that the strong seed dormancy is an accumulative result of pre-existing variations in common wheat and new mutations during de-domestication. For example, seed dormancy in weedy rice and Tibetan semi-wild wheat is likely associated with the selection of pre-existing functional alleles related to pericarp color, although the pericarp color of rice and wheat is controlled by different Rc genes (i.e.…”
Section: Comparison Of the De-domestications Of Rice And Wheatmentioning
confidence: 99%
See 1 more Smart Citation
“…from Sinkiang, and Cayazheda 29 (CY, T. aestivum ssp. tibetanum Shao) from Tibet [28]. The other divergent parent was British dwarf cultivar Hussar (HU), which is a good quality cultivar [37].…”
Section: Plant Materials and Experimental Designmentioning
confidence: 99%
“…characterized by a long glume, and the Yunnan hulled wheat, or "Tiekemai", (T. aestivum ssp. yunnanense King) named for its very hard and tough glumes which adhere to the grains [26][27][28]. The unique semi-wild wheat subspecies in China have a primitive chromosomal constitution, which is crucial to probe the effect of domestication on processing quality in wheat breeding [26].…”
Section: Introductionmentioning
confidence: 99%